Hubungan Dukungan Keluarga dengan Kepatuhan Ibu Hamil Melaksanakan Pemeriksaan Antenatal Care di Wilayah Kerja Ponkesdes Alun-Alun Lumajang - Lindasari, Ike Kurnia; Hamim, Nur; Ermawati, Iit (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Every pregnant woman will face risks that can threaten her life. Therefore, every pregnant woman needs care during her pregnancy through antenatal care checks. Family support is very important to prevent unwanted conditions such as risky pregnancies, and this can be achieved by fulfilling complete antenatal care visits. This study aims to determine the relationship between family support and the compliance of pregnant women in carrying out antenatal care examinations in the Ponkesdes Alun-Alun Lumajang This study was a correlational design with a cross sectional approach. The population in this study were all pregnant women in the Ponkesdes Alun- Alun involving 31 participants. The sampling technique was a simple random sampling. Data collected was a data collection sheet. Data were analyzed using Predictive Analytics SoftWare Version 18 with the spearman rho test at a significance level of <0.05. The results showed that pregnant women in the working area of ​​Ponkesdes Alun-Alun Lumajang more than half (58.1%) received less family support and more than half (54.8%) had a low level of compliance of pregnant women in carrying out antenatal care examinations. The results of statistical analysis showed that there was a relationship between family support and the compliance of pregnant women in carrying out antenatal care examinations with a strong positive correlation level (p-value = 0.000 (α<0.05); r = 0.856). Family support forms a close relationship so that it can increase the satisfaction of pregnant women, and increase the ability of pregnant women to have a healthy pregnancy, and pregnant women with family dysfunction are more likely to be isolated and lead to negative attention.